Adaptação ventricular esquerda em cães de pastoreio - Martins, Raimy Costa (2017)
The "athlete's heart" is the term designed to characterize functional and anatomic cardiac adaptations secondary to intense and prolonged physical training in humans and animals. The echocardiogram plays a fundamental role in distinguishing the physiological adaptations secondary to exercise, also, the recent techniques introduced as Speckle Tracking Echocardiography have allowed us to obtain relevant information regarding cardiac function in human athletes. The aim of this study was to evaluate the structure and systolic function of the left ventricle of dogs practicing herding for at least four months, five to six times a week, from four to eight hours a day using echocardiography. For this, 31 dogs were divided into two groups: herding group (GP, n=15) and sedentary group (GS, n=16), evaluated in a single moment, at rest, and then submitted the multivariate analysis of variance (ANOVA), two by two, at the level of significance at 95% (p<0,05) and tendency to 90% (p<0.1). The GP dogs showed higher values of internal diameter of the ventricle at the end of systole (GP: 2,72 ± 0,09; GS: 2,43 ± 0,09; P<0,034), indicating isotonic predominance of this activity. At respect functional adaptations variables, systolic volume was higher in GP (GP: 28,51 ± 2,20; GS: 22,13 ± 2,17; P<0,049), differently from myocardial performance index of the left ventricle (GP: 0,37 ± 0,03; GS: 0,46 ± 0,03; P<0,028) and septal systolic moviment to GS (GP: 0,13 ± 0,01; GS: 0,15 ± 0,01; P<0,044). By means of the Ste technique, it was possible to observe a decrease in the strain and or strain rate values in GP dogs, in the radial, circumferential, longitudinal and transverse directions in relation to GS, indicating a lower need for myocardial deformation to maintain systolic function. The results indicate that the conventional echocardiographic variables (structural and functional) and tissue, obtained by the STe technique, were complementary and essential for the understanding of cardiovascular adaptations in herding dogs.